Impact of country-level cultural development on the achievement of sustainable development goals - Titko, Jelena; Svirina, Anna; Astike, Kristina; Uzule, Kristine; Shina, Inga; Zarina, Vita (Business, Management and Economics Engineering, 2023)
Purpose – The goal of the research was to test a general assumption about culture contribution to sustainable development via the relationship between culture-related indices and the achievement of specific sustainable development goals.Research methodology – Linear regression analysis along with robustness testing was used to test research hypotheses. The data set is represented by 19 explanatory variables and 2 dependent variables, which are proxies for sustainable developments goals Decent Work and Economic Growth and Industry, Innovation and Infrastructure – Innovation index and Global competitiveness index. The data were collected from 27 European countries for the period 2011–2020.Findings – Statistical analysis revealed relationship between sustainable development indices and culture development of European countries. Decent Work and Economic Growth demonstrated more significant relationship to cultural development than the Industry, Innovation and Infrastructure Development.Research limitations – The findings are limited by the fact that some variables were missing.Practical implications – The outcomes of the research allow to define the structure of relationship between sustainable development goals and cultural development indicators.Originality/Value – The research results have indicated that the achievement of sustainable development goals Decent Work and Economic Growth and Industry, Innovation and Infrastructure Development are affected by the level of cultural development.